A Collaborative Approach to Coordinating Calculus 1 to Improve Student Outcomes. Issue 3 (28th May 2021) - Mingus, Tabitha T. Y.; Koelling, Melinda
ABSTRACT: Faced with students failing to complete Calculus 1 at rates of almost 50%, the Department of Mathematics at Western Michigan University addressed the lack of progression of STEM majors through this gateway course and, thus, through their intended majors. In this case study, we describe the four-year process of redesigning our single variable Calculus 1 course. We coordinated instruction with a changing, highly collaborative instructional team of faculty and graduate students. Conversations among team members have been driving changes in instruction and assessment, and collaborative coordination is helping institutionalize the successful elements of the redesign. At the end of the paper, we describe the major take-aways we have gained as a result of this experience.